Optical studies on a single GaAs laterally coupled quantum dot in comparison with an uncoupled quantum dot - Kim, Heedae; Song, Jin Dong (ELSEVIER SCIENCE BV, 2018)
We performed spectroscopy studies on a single GaAs laterally coupled quantum dot and an uncoupled quantum dot. Photoluminescence spectra confirmed the presence of optical coupling in the coupled quantum dot through dipole-dipole interactions. The optical coupling was investigated in terms of the integrated photoluminescence intensities and redshift of emission energies as the excitation power was increased. The excitation intensity was increased with linearly polarized light in the lateral coupling direction 1 (1) over bar0, which resulted in excitons X-1 and X-2 of the coupled quantum dot showing a clear photoluminescence peak shift to lower energy with drastically different power factors. These results were obtained by integrating the PL spectrum and comparing it to that of a single quantum dot. We also found that the decay rates of X-1 and X-2 in the coupled quantum dot increased significantly as a consequence of overlap of electron and hole wavefunctions extended via optical coupling in individual dots of the coupled quantum dot system. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: DROPLET EPITAXY; RING; MOLECULES; EXCITON; STATES